Descoberta dinâmica, sensível ao contexto, de serviços web - Silva, Victor Gomes da (2014)
Currently the Internet is one of the biggest media in the world, turning and accelerating forms of publishing and content consumption. At the same time, users have become more demanding for the content and the consumption of large amount of information that the Web provides. Since its inception, the Internet has gone through some phases, showing that the changes take place according to the requirements of users, such as the evolution of the Web to Web 2.0 which is marked by the interaction, collaboration and communication among users, who can publish and share their own content on the Internet. This reality has led to the need to build applications that support the large amount of information to users and different devices, arranged in multiple contexts of use, increasing the demand for software in Ubiquitous Computing, in which access to applications occurs anywhere, anytime and from different devices. The construction and maintenance of specific versions of applications for each context of use have become difficult due to the diversity of devices, users, access networks and other factors to be considered. Moreover, it is necessary for applications to be developed so that the compatibility of the contextual features of the environment in which they operate is maintained and does not impair the interaction of users. Motivated to overcome these challenges this work presents an architecture for Dynamic Discovery of Context-Sensitive Web Services that supports the creation of ubiquitous applications adaptive to different contexts. Applications driven by this architecture meet varying access networks in different contexts. The proposed architecture is based on the concepts of Service Oriented Architecture. The proposed architecture was evaluated with a case study and experimentation with users. The computational support that employs the proposed architecture has the advantage of discovering services at run time and can vary according to the context of the access network.